Podcast Politik Indonesia: Upaya Mencari Calon Presiden Indonesia 2024 - Redi Panuju (Unitri Press, 2023)
This article aims to reveal the role of political podcasts in political communication, especially regarding preparations for the 2024 Indonesian Presidential and Vice-President elections. There are two categories of political podcasts based on their creators, namely political podcasts made by private television stations and political podcasts made by individuals. The television station's political podcast is a recycled product of a talk show broadcast that has been broadcast before, after editing certain parts and formatting a video, then uploading it on the YouTube channel. Meanwhile, individual Podcasts are the result of individual production with an interview format between the Host and the resource persons discussing certain themes. The results of the interview recording were uploaded via the YoutTube channel. Podcast narrative becomes qualitative data that shows certain characteristics. The methods used are case studies and social ethnography. The research procedure begins with interpreting the results of the conversations into qualitative data coding based on certain coding. The results of the study show that podcasts made by certain television stations are more careful in conducting interviews, limiting themselves to themes of party structure functions in finding pairs of candidates for President and Vice President, while podcasts made by individuals are more flexible in elaborating thoughts, feelings, and visions for the future. front of the presidential candidate. Abstrak Artikel ini bertujuan mengungkap peran podcast politik dalam komunikasi politik, terutama menyangkut persiapan pemilihan Presiden dan Wakil Presiden Indonesia tahun 2024. Ada dua kategori podcast politik berdasarkan pembuatnya, yakni podcast politik yang di buat Stasiun Televisi Swasta dan podcast politik yang dibuat oleh perorongan. Podcast politik stasiun televisi merupakan hasil daur ulang dari siaran talk show yang telah disiarkan sebelumnya, setelah diedit bagian tertentu dan diformat video, selanjutnya diuanggah di channel YouTube. Sedangkan Podcast perorongan merupakan hasil produksi individu dengan format wawancara antara Host dengan nara sumber membicarakan tema tema tertentu. Hasil rekaman wawancara tersebut diuanggah melalui kanal YoutTube. Narasi Podcast menjadi data kualitatif yang memperlihatkan karakteristik tertentu. Metode yang digunakan adalah studi kasus dan etnografi sosial. Prosedur penelitian dimulai dengan memaknai hasil percakapan menjadi kodensasi data kualitatif berdasarkan koding tertentu. Hasil penelitian menunjukkan bahwa podcast yang dibuat oleh StasiunTelevisi tertentu lebih hati hati dalam melakukan wawancara, membatasi diri tentang tema tema fungsi struktur partai dalam mencari pasangan Calon Presiden dan Wakil Presiden, sementara Podcast yang dibuat oleh perseorangan lebih leluasan mengelaborasi pikiran, perasaan, dan visi ke depan Calon Presiden.